Endothelial Nitric Oxide Synthase Enzyme Gene Polymorphism (Exon 7, 894 Gâ†’T, Glu298Asp) in BehÃ§et’s Patients: a Case-Control Study - Gençoğlu, Åžule (Journal of Pakistan Association of Dermatologists, 2023)
Background The etiology of BehÃ§et’s disease (BD) remains partially unknown and the eNOS gene polymorphism indicated a particular characteristic of vasculitis in the disease progress. Methods The study was planned as a case-control study. The BD group included 36 patients, 22 (61.1%) female patients and 14 male (38.9%), aged 20-70 years while the control group consisted of 36 volunteers, 20 (55.6%) female volunteers and 16 (44.4%) male with similar age distributions. Polymerase Chain Reaction (PCR) - restricted fragment length (RFL) polymorphism analysis was used to determine Glu298Asp variants in all samples. Results In the RLP analysis conducted in the BD group, the TT (5.6%) genotype was detected in 2 patients, the GG (55.6%) in 20, and the GT genotype in 14 (38.9%). While the TT genotype was not found in the control group, the GG genotype was detected in 30 individuals (83.3%) and the GT genotype in 6 individuals (16.7%). The GG genotype was significantly higher in the control group and the GT genotype significantly higher in the GH group (p= 0.027). While 18 (25.0%) T alleles and 54 (75.0%) G alleles were detected in the BD group, 6 (8.3%) T alleles and 66 (91.7%) G alleles were detected in the control group (p=0.007). The risk of having the T allele in patients with BehÃ§et’s disease was 3.7 times higher when compared to that of the control group (OR=3.7, 95% Cl for OR: 1.36-9.88, p<0.05). Conclusions A significant association of the Glu298Asp polymorphism of the eNOS gene with BH in the Turkish population is found.